The Integration Model of Islam and Science Learning in Islamic Education and Character Building at SMK Muhammadiyah 8 Paciran - Muhammad Hambal Shafwan; Roy Imam Syah (CV. Zamron Pressindo, 2024)
This research aims to discuss: (1) How is the Learning Model of Islamic Education at SMK Muhammadiyah 8 Paciran; (2) How is the Implementation of Islamic and Science Integration Learning Model in Islamic Education Class X at SMK Muhammadiyah 8 Paciran; (3) How is the Implication of Islamic and Science Integration Learning Model on Islamic Education Subject in Class X at SMK Muhammadiyah 8 Paciran This research uses a descriptive qualitative approach. Data collection techniques used interviews, participant observation and documentation. Data analysis consisted of data reduction, data presentation and conclusion drawing. Data validity checking was done through triangulation of sources and techniques. The results of the study concluded that the research highlighted that first: the learning model of PAI and Budi Pekerti at SMK Muhammadiyah 8 Paciran is still conventional and less active for students. Second: With the implementation of the Islamic and science integration learning model, there is a significant change in the learning approach. The multidisciplinary approach applied allows students to relate the teachings of the Qur'an to various disciplines, resulting in a more meaningful understanding of Islamic religion and scientific concepts. Third: In addition, the model increases student engagement and makes learning conditions more conducive, strengthening critical skills as well as students' overall learning motivation. Thus, the implementation of this model promises significant improvements in the effectiveness of PAI and Budi Pekerti learning at SMK Muhammadiyah 8 Paciran.